Alterations of DNA methylation in parathyroid tumors. (5th July 2018) - Guarnieri, Vito; Muscarella, Lucia Anna; Verdelli, Chiara; Corbetta, Sabrina
Abstract: Parathyroid tumors are common endocrine neoplasias associated with primary hyperparathyroidism, a metabolic disorder characterized by parathormone hypersecretion. Parathyroid neoplasia are frequently benign adenomas or multiple glands hyperplasia, while malignancies are rare. The epigenetic scenario in parathyroid tumors has just begun to be decoded: DNA methylation, histones and chromatin modifiers expression have been investigated so far. The main findings suggest that DNA methylation and chromatin remodeling are active and deregulated in parathyroid tumors, cooperating with genetic alterations to drive the tumor phenotype: the tumor suppressors menin and parafibromin, involved in parathyroid tumorigenesis, interact with chromatin modifiers, defining distinct epigenetic derangements. Many epigenetic alterations identified in parathyroid tumors are common to those in human cancers; moreover, some aspects of the epigenetic profile resemble epigenetic features of embryonic stem cells. Epigenetic profile may contribute to define the heterogeneity of parathyroid tumors and to provide targets for new therapeutic approaches. Highlights: Parathyroid tumors display hypermethylation of the CpG islands in the promoter of specific genes. Hypermethylation occurs mainly in aggressive and malignant parathyroid tumors. Parathyroid pivotal genes are not regulated by DNA methylation. The tumor suppressor genes lost in parathyroid tumorigenesis interact with a number of chromatin modifiers. Chromatin modifiers deregulation in parathyroid tumors is similar to that in human cancers and in embryonic stem cells.